2022
DOI: 10.1136/bmj.o2725
|View full text |Cite
|
Sign up to set email alerts
|

RSV: UK to examine whether to offer monoclonal antibody routinely to all babies

Abstract: Nirsevimab has received regulatory approval in the UK, and researchers will now assess its benefits in protecting babies from serious illness from respiratory syncytial virus, as Jacqui Wise reports

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…Respiratory syncytial virus (RSV) is a common seasonal cause of acute lower respiratory tract infection (LRTI) in young children, 1 and a leading cause of infant hospitalizations. [2][3][4][5] A novel RSV-neutralizing monoclonal antibody, nirsevimab, has recently been approved in the EU (2022), UK (2022), Canada (2023), and the USA (2023), [6][7][8][9] to prevent RSV lower respiratory tract disease in neonates and infants during their first RSV season. The safety and efficacy of nirsevimab in protecting against medically attended RSV LRTIs was demonstrated in a placebo-controlled phase IIb study 10 and phase III (MELODY) study 11,12 in healthy preterm and term infants (i.e., those not currently eligible for RSV prophylaxis with palivizumab) in their first RSV season.…”
Section: Introductionmentioning
confidence: 99%
“…Respiratory syncytial virus (RSV) is a common seasonal cause of acute lower respiratory tract infection (LRTI) in young children, 1 and a leading cause of infant hospitalizations. [2][3][4][5] A novel RSV-neutralizing monoclonal antibody, nirsevimab, has recently been approved in the EU (2022), UK (2022), Canada (2023), and the USA (2023), [6][7][8][9] to prevent RSV lower respiratory tract disease in neonates and infants during their first RSV season. The safety and efficacy of nirsevimab in protecting against medically attended RSV LRTIs was demonstrated in a placebo-controlled phase IIb study 10 and phase III (MELODY) study 11,12 in healthy preterm and term infants (i.e., those not currently eligible for RSV prophylaxis with palivizumab) in their first RSV season.…”
Section: Introductionmentioning
confidence: 99%
“…Nirsevimab, a new monoclonal antibody, has been approved for the prevention of RSV‐associated LRTI in both preterm and full‐term infants during their first RSV season 9–12 . It has shown greater potency in reducing RSV infection and a more extended half‐life than palivizumab 13 .…”
Section: Introductionmentioning
confidence: 99%
“…5,8 Nirsevimab, a new monoclonal antibody, has been approved for the prevention of RSV-associated LRTI in both preterm and full-term infants during their first RSV season. [9][10][11][12] It has shown greater potency in reducing RSV infection and a more extended half-life than palivizumab. 13 Clinical trials revealed a decrease in the incidence of RSV-LRTI and hospitalization after a single intramuscular dose of nirsevimab, exhibiting a favorable safety profile.…”
mentioning
confidence: 99%
“…Recent studies have demonstrated efficacy in reducing medically attended RSV infection, with a relative risk reduction of 79.5% (95% CI 65.9 to 87.7) 41–44. Further large-scale studies into use of nirsevimab are ongoing, and as of yet the UK has not released guidance on its use; however, given the reduction in dosing requirements, it is hoped that nirsevimab may prove a more attractive option for wide-scale clinical use than palivizumab 45…”
Section: Introductionmentioning
confidence: 99%